2007
DOI: 10.1080/10862960701613086
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Information Online: Knowledge, Navigation and Learning Outcomes

Abstract: Research suggests that the World Wide Web (WWW) represents the intersection of at least two domains: content and technology. This investigation was designed to examine the relationship between prior knowledge and WWW browsing outcomes (i.e., navigation behavior and knowledge gain) within the context of a genetics Web site. Students randomly assigned to a treatment group were given a prereading activity designed to increase their prior knowledge within the domain of genetics. This group demonstrated significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 37 publications
0
33
0
1
Order By: Relevance
“…One key defining feature of navigation is that learners are given a general task after learning from hypermedia, such as writing an essay or answering specific questions, rather than being asked to search for specific information. As with search, the navigation literature is small (Lawless et al 2007), but has nonetheless converged on a number of main findings that are extremely similar to those in the search literature. First, prior knowledge is related to navigational patterns (moves).…”
Section: Differentiating Between Search and Navigationmentioning
confidence: 87%
See 1 more Smart Citation
“…One key defining feature of navigation is that learners are given a general task after learning from hypermedia, such as writing an essay or answering specific questions, rather than being asked to search for specific information. As with search, the navigation literature is small (Lawless et al 2007), but has nonetheless converged on a number of main findings that are extremely similar to those in the search literature. First, prior knowledge is related to navigational patterns (moves).…”
Section: Differentiating Between Search and Navigationmentioning
confidence: 87%
“…First, prior knowledge is related to navigational patterns (moves). For example, Lawless et al (2007) found that college students with more prior knowledge used fewer menus, used more hyperlinks, and viewed more graphical representations. Second, for undergraduate students prior knowledge is associated with more often finding key pages and less often visiting irrelevant pages, and these patterns are associated with better learning outcomes (Naumann et al 2008;Schrader et al 2008).…”
Section: Differentiating Between Search and Navigationmentioning
confidence: 99%
“…Studies of the navigational behaviour of older students indicate that prior knowledge of the content domain enables students to navigate more easily through information in hypermedia environments, and to make more efficient and effective selections of content, resulting in better comprehension of material than those with little prior knowledge. This effect was enhanced when students were also familiar with the online hypermedia contexts in their content areas (Lawless et al 2007;Lawless and Schrader 2008).…”
Section: Hypertext and Reading Comprehensionmentioning
confidence: 99%
“…Acquisition of knowledge during search has also received attention. Lawless et al (2007) investigated the relationship between prior knowledge and the acquisition of new knowledge during web browsing by treating one group of participants with reading selected to enhance their domain knowledge prior to the search. Pre-and post-test knowledge scores of the treated and untreated groups showed that participants in the treatment group significantly increased their knowledge score.…”
Section: Level Of Knowledgementioning
confidence: 99%